Synthesis, characterization and properties of low density polyethylene filled with reduced graphite oxide - Toh, Guat Yee (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
The aim of this work focuses on preparation and characterization of graphite oxide nanoplatelet as filler that incorporate into the low density polyethylene thin film nanocomposite. Emphasis is given on the synthesis of the graphite oxide and reduced graphite oxide nanoplatelet, responses of bare reduced graphite oxide that performed in the thin film polyethylene nanocomposites. The uniqueness of this work is to simplify the synthesis process of reduced graphite oxide through Hummer's method and also, to fabricate low density polyethylene based thin film nanocomposites with the incorporation of reduced graphite oxide by using simple solvent cast method. Following are the three objectives of the work ; to synthesis graphite oxide (GO) using simplified Hummer's method and further reduces into reduced graphite oxide (rGO) through chemical reduction process in physico-chemical analysis ; to study the effect of rGO content on structural properties, tensile properties, thermal behaviour and gas barrier properties towards the LDPE ; to investigate the effect of thermal and ultraviolet light degradations of LDPE after incorporation with rGO.